REGULATION INFLUENCE OF BULBUS OLFACTORIUS AT THE RESPIRATORY NEURONS IN HYPOXIA CONDITIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
Under conditions of oxygen deficiency the influence of electrical stimulation Bulbus olfactorius on the impulse activity of bulbar respiratory neurons was studied. Under conditions of normoxia both activation and inhibition of impulse activity of bulbar respiratory neurons are observed with predominance activatory action. At the initial stage of oxygen deficiency on the hypoxic activation background the activatory action of Bulbus olfactorius is less expressed than under conditions of normoxia. At the second stage of hypoxia the activatory influence of this nucleus was significant.
Keywords: $Bulbus olfactorius$; bulbar respiratory neurons; hypoxia